2017
DOI: 10.24326/asphc.2017.6.6
|View full text |Cite
|
Sign up to set email alerts
|

ONTOGENETIC VARIABILITY IN THE QUANTITY AND QUALITY OF WINTER SAVORY (Satureja montana L.) HERB YIELD

Abstract: The chemical composition and activity of herbal raw material depend, among others, on ontogenetic variability. The present study investigated the effect of harvest date of winter savory (Satureja montana L.) herb and plant age on fresh and dry herb yield as well as on the content of L-ascorbic acid, carotenoids, chlorophylls, essential oil, flavonoids and tannins. S. montana herb from a one-and two-year-old plantation was harvested in June (vegetative stage), July (beginning of flowering), August (full floweri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
6
22
0
1
Order By: Relevance
“…The most important constituents of essential oils primarily belong to seven chemical groups: monoterpenes (α-thujene, sabinene, α-pinene, β-myrcene, β-pinene, α-terpinene, limonene, α-phellandrene, terpinolene), bicyclic monoterpenoids (cis & trans -sabinene hydrate), acyclic monoterpenoids (linalool), cyclic monoterpenoids (rose oxide b, 2-cyclohexen-1-ol, menthone, menthone, citronellal, isomenthone, menthan-2-one < cis-ρ- > , phenol/2-methoxy-3-(2-propenyl)-, citronellyl formate, citral < dimethoxy-(z)- > , thymol, citronellyl acetate, neryl acetate, nepetalactone < 4aα,7α,7aβ- >), alcoholic monoterpenoids (terpinen-4-ol, citronellol, geraniol), sesquiterpenes (β-elemene, caryophyllene, germacrene D, γ-cadinene, α-cadinol) and sesquiterpenoids (citronellyl propanoate, citronellyl butanoate, elemol, phenyl ethyl tiglate < 2- > , eudesmol < 10-epi-γ- > , γ-eudesmol, citronellyl tiglate) (Table 2 ). The chemical constituent profile of O. majorana and O. vulgare isolated essential oils remained in harmony with earlier reported studies 49 , 86 . The components of C. winterianus, P. graveolens, and N. cataria are similar to the earlier reported studies 15 , 25 , 51 , 53 , 68 , 87 .…”
Section: Resultssupporting
confidence: 90%
“…The most important constituents of essential oils primarily belong to seven chemical groups: monoterpenes (α-thujene, sabinene, α-pinene, β-myrcene, β-pinene, α-terpinene, limonene, α-phellandrene, terpinolene), bicyclic monoterpenoids (cis & trans -sabinene hydrate), acyclic monoterpenoids (linalool), cyclic monoterpenoids (rose oxide b, 2-cyclohexen-1-ol, menthone, menthone, citronellal, isomenthone, menthan-2-one < cis-ρ- > , phenol/2-methoxy-3-(2-propenyl)-, citronellyl formate, citral < dimethoxy-(z)- > , thymol, citronellyl acetate, neryl acetate, nepetalactone < 4aα,7α,7aβ- >), alcoholic monoterpenoids (terpinen-4-ol, citronellol, geraniol), sesquiterpenes (β-elemene, caryophyllene, germacrene D, γ-cadinene, α-cadinol) and sesquiterpenoids (citronellyl propanoate, citronellyl butanoate, elemol, phenyl ethyl tiglate < 2- > , eudesmol < 10-epi-γ- > , γ-eudesmol, citronellyl tiglate) (Table 2 ). The chemical constituent profile of O. majorana and O. vulgare isolated essential oils remained in harmony with earlier reported studies 49 , 86 . The components of C. winterianus, P. graveolens, and N. cataria are similar to the earlier reported studies 15 , 25 , 51 , 53 , 68 , 87 .…”
Section: Resultssupporting
confidence: 90%
“…In this respect, [21], [22], and [23] mentioned that the increase in potassium fertilizer levels resulted in reducing nitrate accumulation in some vegetable crops. In addition to that [19] and [24] reported that the increase in K fertilization reduces nitrate accumulation in plants. "The application of double rate of K and phosphorus contributed to a reduction in nitrate content of rocket plants even at high rates of N" [25].…”
Section: Ash N and No3 Concentration Of Forage Sorghummentioning
confidence: 89%
“…There was no significant difference(p>0.005) of applications of Potassium sulfate on NO 3 of forage sorghum (Table 1). [19] reported that "the application of potassium significantly contributed to the amount of NO 3 in edible parts of rockets, but significant differences only related to the rate of K. The increasing amount of K caused a reduction in the amount of N-NO 3 , but no significant differences were found in the series with the medium and the highest rates of K. Increased potassium fertilization has an effect on a reduction in nitrate accumulation in plants". Moreover, comparable results were obtained by [20] who stated that "nitrate contents in vegetables were raised with increasing N supply but decreased with potassium application, especially at high N application levels".…”
Section: Ash N and No3 Concentration Of Forage Sorghummentioning
confidence: 99%
“…Eruca is a family of plants recognized to offer many medicinal and therapeutic characteristics. [36,37] Such as anti-ulcer, [38]. Liver detoxification [33], antibacterial, antidiabetic, antihypertensive, antioxidant and antiplatelet action as it prevents thrombus formation [16].…”
Section: Rocket Medicinal Applicationmentioning
confidence: 99%